Relative impact of three growth conditions on the Escherichia coli protein acetylome - Gema Lozano-Terol; Riccardo Zenezini Chiozzi; Julia Gallego-Jara; Rosa Alba Sola-Martínez; Adrián Martínez Vivancos; Álvaro Ortega; Albert J.R. Heck; Manuel Cánovas Díaz; Teresa de Diego Puente (iScience, 2024)
Summary: Nε-lysine acetylation is a common posttranslational modification observed in Escherichia coli. In the present study, integrative analysis of the proteome and acetylome was performed using label-free quantitative mass spectrometry to analyze the relative influence of three factors affecting growth. The results revealed differences in the proteome, mainly owing to the type of culture medium used (defined or complex). In the acetylome, 7482 unique acetylation sites were identified. Acetylation is directly related to the abundance of proteins, and the level of acetylation in each type of culture is associated with extracellular acetate concentration. Furthermore, most acetylated lysines in the exponential phase remained in the stationary phase without dynamic turnover. Interestingly, unique acetylation sites were detected in proteins whose presence or abundance was linked to the type of culture medium. Finally, the biological function of the acetylation changes was demonstrated for three central metabolic proteins (GapA, Mdh, and AceA).